The dark side of non-fungible tokens: understanding risks in the NFT marketplace from a fraud triangle perspective - Nitin Upadhyay; Shalini Upadhyay (Financial Innovation)
Abstract This study investigates the dark side of the non-fungible token (NFT) marketplace, with a focus on understanding the risks, and underlying factors driving fraud in the NFT ecosystem. Using the fraud triangle framework, this study examines pressure, opportunity, and rationalization from individual and organizational perspectives. The research provides a comprehensive understanding of the contributing factors to NFT marketplace fraud by analyzing the reasons behind fraudulent actions. A conceptual framework is developed that includes ten propositions to aid in understanding the complexity of this issue. This study’s outcomes will assist policymakers in crafting efficient approaches to mitigate fraud within the NFT marketplace.